2019
DOI: 10.1097/fch.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Concordance and Discordance of the Knowledge, Understanding, and Description of Children's Experience of Food Insecurity Among Hispanic Adults and Children

Abstract: Food insecurity is highly detrimental for children, who experience food insecurity differently than do adults. We aimed to understand concordance and discordance of adults' and children's knowledge, understanding, and description of children's experience of food insecurity. In-depth interviews were conducted with the primary caregiver, another caregiver, and a child 9 to 16 years of age in 16 Hispanic families at risk of food insecurity in South Carolina. Adults often lacked knowledge of the food insecurity ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…A previous study demonstrated that the two-item tool was sensitive, specific and valid when tested in a sample of 30 098 families with young children of which 23 % were food insecure (17) , but these two items may not capture the experience of all individuals in the household, particularly children. Although parents attempt to protect their children from food insecurity, children are often aware of food insecurity and take responsibility for it (27) . Children's experiences of food insecurity are often not known by parents (27) .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the two-item tool was sensitive, specific and valid when tested in a sample of 30 098 families with young children of which 23 % were food insecure (17) , but these two items may not capture the experience of all individuals in the household, particularly children. Although parents attempt to protect their children from food insecurity, children are often aware of food insecurity and take responsibility for it (27) . Children's experiences of food insecurity are often not known by parents (27) .…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes that the measurement of household-level FI may not be a true reflection of adolescents FI and should be measured separately. Adolescents are at an age where they can sense the stress in the house and try to play their part in buffering the effects of FI [25]. Literature reports that adolescents voluntarily cut-down their portion size during food shortages which at times go unnoticed by adults of the family [38].…”
Section: Discussionmentioning
confidence: 99%
“…Frongillo explained a few reasons for parents' lack of information regarding adolescent FI through their qualitative work. The author wrote that when parents reduce their portion sizes, do not discuss the FI situation of households with their children, they assume that they have protected the children from hunger and anxiety of FI [25]. Hence, adolescents' FI is under-reported by adults of the household.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations